2018
DOI: 10.1002/ajmg.a.38601
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, BTD gene mutations, and their functional studies of eight symptomatic patients with biotinidase deficiency from Southern China

Abstract: Biotinidase (BTD) deficiency is a rare autosomal recessive metabolic disease, which develops neurological and cutaneous symptoms because of the impaired biotin recycling. Pathogenic mutations on BTD gene cause BTD deficiency. Clinical features and mutation analysis of Chinese children with BTD deficiency were rarely described. Herein, for the first time, we reported the clinical features, BTD gene mutations and their functional studies of eight symptomatic children with BTD deficiency from southern China. Fati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…This is consistent with Wolf et al's study conducted in the United States of America (USA), whereas one patient was found to have a c.1361A>C (p.Tyr454Cys) mutation with a complete absence of the biotinidase activity (0.0 nmol/min/mL) [22]. The last detected mutation in our cohort was c.235C>T (p.Arg79Cys) in exon 2, which is common in different populations from South China [23], Iran [24], Poland [25], Turkey [17,26,27], United States [22], and Sweden [28]. The Iranian, Turkish, and American children were found to have an enzyme activity of 0.11, 0.13, and 0.0 nmol/min/mL, respectively [22,24,26].…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with Wolf et al's study conducted in the United States of America (USA), whereas one patient was found to have a c.1361A>C (p.Tyr454Cys) mutation with a complete absence of the biotinidase activity (0.0 nmol/min/mL) [22]. The last detected mutation in our cohort was c.235C>T (p.Arg79Cys) in exon 2, which is common in different populations from South China [23], Iran [24], Poland [25], Turkey [17,26,27], United States [22], and Sweden [28]. The Iranian, Turkish, and American children were found to have an enzyme activity of 0.11, 0.13, and 0.0 nmol/min/mL, respectively [22,24,26].…”
Section: Discussionsupporting
confidence: 93%
“…BTD encodes the biotinidase protein, which recycles protein-bound biotin by cleaving biotin (biotinepsilon-lysine) that is a normal product of carboxylase degradation, resulting in regeneration of free biotin [24]. BTD-deficiency is associated with various diseases [25]. In our current study, we found that BTD was downregulated in iCCA, and was positively associated with the OS of iCCA patients.…”
Section: Discussionsupporting
confidence: 53%
“…Recently, five novel mutations and one heterozygous linkage for the c.250-1G>C and c.878dupT variants were discovered in eight symptomatic patients from China, resulting in decreased protein expression due to structural damage and affecting BTD enzyme activity ( 15 , 16 ). In the present study, using homology modeling of BTD, we confirmed that replacement of ARG with CYS is deleterious and results in a non-functional BTD enzyme.…”
Section: Discussionmentioning
confidence: 99%